Information theft prevention : theory and practice - Okeke, Romanus Izuchukwu; Shah, Mahmood, 1971- (Routledge studies in innovation, organization and technology, 2016)
As retail businesses migrate to the digital realm, internal information theft incidents continue to threaten on-line and off-line retail operations. The evolving propagation of internal information theft has surpassed the traditional techniques of crime prevention practices. Many business organizations search for internal information theft prevention guides that fit into their retail business operation, only to be inundated with generic and theoretical models. This book examines applicable methods for retail businesses to effectively prevent internal information theft. Information Theft Preventionoffers readers a comprehensive understanding of the current status of the retail sector information theft prevention models in relation to the internationally recognized benchmark of information security. It presents simple and effective management processes for ensuring better information system security, fostering a proactive approach to internal information theft prevention. Furthermore, it builds on well-defined retail business cases to identify applicable solutions for businesses today. Integrating the retail business operations and information system security practices, the book identifies ways to coordinate efforts across a business in order to achieve the best results. IT security managers and professionals, financial frauds consultants, cyber security professionals and crime prevention professionals will find this book a valuable resource for identifying and creating tools to prevent internal information theft.